Electronic Spectral Line Shape of a Diatomic Molecule - Reza Islampour; Ali Maghari (Iranian Journal of Chemistry & Chemical Engineering, 1988)
The electronic absorption spectral line shape of a diatomic molecule with harmonic potential curves is calculated using the time correlation function formalism. Both the equilibrium shift and the frequency shift of the two linking electronic states ate taken into account. The spectrum is also calculated using the cumulated expansion which is related to the correlation function of the time-dependent energy gap between the two electronic states.